Lipoplex‐Mediated Single‐Cell Transfection via Droplet Microfluidics. Issue 40 (10th September 2018) - Li, Xuan; Aghaamoo, Mohammad; Liu, Shiyue; Lee, Do‐Hyun; Lee, Abraham P.
Abstract: While lipoplex (cationic lipid‐nucleic acid complex)‐mediated intracellular delivery is widely adopted in mammalian cell transfection, its transfection efficiency for suspension cells, e.g., lymphatic and hematopoietic cells, is reported at only ≈5% or even lower. Here, efficient and consistent lipoplex‐mediated transfection is demonstrated for hard‐to‐transfect suspension cells via a single‐cell, droplet‐microfluidics approach. In these microdroplets, monodisperse lipoplexes for effective gene delivery are generated via chaotic mixing induced by the serpentine microchannel and co‐confined with single cells. Moreover, the cell membrane permeability increases due to the shear stress exerted on the single cells when they pass through the droplet pinch‐off junction. The transfection efficiency, examined by the delivery of the pcDNA3‐EGFP plasmid, improves from ≈5% to ≈50% for all three tested suspension cell lines, i.e., K562, THP‐1, Jurkat, and with significantly reduced cell‐to‐cell variation, compared to the bulk method. Efficient targeted knockout of the TP53BP1 gene for K562 cells via the CRISPR (clustered regularly interspaced short palindromic repeats)–CAS9 (CRISPR‐associated nuclease 9) mechanism is also achieved using this platform. Lipoplex‐mediated single‐cell transfection via droplet microfluidics is expected to have broad applications in gene therapy and regenerative medicine by providing high transfection efficiency and low cell‐to‐cell variation for hard‐to‐transfect suspension cells. Abstract : A single‐cell, droplet‐microfluidics approach enabling order‐of‐magnitude higher (increase from ≈5% to ≈50%) lipoplex‐mediated transfection (lipofection) efficiency for hard‐to‐transfect suspension cells is reported. The lipofection efficiency and consistency is improved because monodisperse lipoplexes are rapidly generated via chaotic mixing and co‐confined in picoliter droplets with single cells, whose membrane permeability is increased while squeezing through the orifice for droplet formation.